Development of Deradicalization Integrated Islamic Education Support Books - Hisban Thaha; Edhy Rustan; Mawardi Mawardi (Jurnal Iqra' : Kajian Ilmu Pendidikan, 2021)
The aim of article developt books to support Islamic Education learning as an effort to prevent the development of religious radicalism in madrasah aliyah. This research was conducted with a mixed-method design. The book development process includes preliminary studies, book development, validation, and testing the effectiveness of integrated teaching materials for the prevention of religious radicalism. Based on the results of the analysis of the needs of several subjects, data was obtained that the development of supporting books on Islamic Education was very necessary for preventing religious radicalization. It can be done by internalizing the deradicalization of religion in Islamic Religious Education (PAI) learning materials. The book was designed according to needs analysis. Pancasila, pluralism, and religious moderation are integrated into learning materials to increase students' belief and belief in Allah SWT which is reflected in attitudes and experiences of worship. The results of due diligence by experts, due diligence by teachers, and students and the results of the FGD show that the product can be declared valid. Also, based on the test results, it was known that supporting books were declared effective, efficient, and have high attractiveness. Thus the supporting books for Islamic Education that have been developed were valid and effective for use in Islamic Education learning for Madrasah Aliyah as an effort to prevent religious radicalism Keywords: Supporting Books, Religious Deradicalization, Book Deradicalization